1976
DOI: 10.1021/bi00646a023
|View full text |Cite
|
Sign up to set email alerts
|

The interaction specificity of peptides with DNA. Evidence of peptide β-sheet-DNA binding

Abstract: Proton magnetic resonance studies (1H NMR) of the interaction of oligopeptide amides of defined sequence (and containing the amino acid, phenylalanine) with salmon sperm DNA are reported. The extent of upfield chemical shifts, deltasigma, and signal line broadening of the aromatic protons (in the presence of excess DNA) are found to depend on the primary sequence and stereochemistry of alpha carbons of the amino acids in the oligopeptide amides. The results obtained with 21 different di-, tri-, tetra-, penta- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1

Year Published

1976
1976
1996
1996

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 35 publications
0
19
1
Order By: Relevance
“…In fact, Gabbay and co-workers, with reporter molecules and peptides containing small aromatic ring systems which could insert a part of their molecule into the bases of DNA (44)(45)(46)(47), suggested that several derivatives could produce a very different effect on helix length and viscosity. One possibility proposed is that these compounds cause a bending of the double helix favouring a partial intercalation and resulting in a slight decrease in length on complex formation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Gabbay and co-workers, with reporter molecules and peptides containing small aromatic ring systems which could insert a part of their molecule into the bases of DNA (44)(45)(46)(47), suggested that several derivatives could produce a very different effect on helix length and viscosity. One possibility proposed is that these compounds cause a bending of the double helix favouring a partial intercalation and resulting in a slight decrease in length on complex formation.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the indole ring is fully inserted between base pairs or partially inserted is still unknown. On the basis of physicochemical and viscosimetric studies, it was suggested that the stacking of tryptophan with bases could induce a bend in the DNA structure as a result of a partial insertion between successive base pairs (Gabbay et al, 1976; Héléne & Maurizot, 1981).…”
mentioning
confidence: 99%
“…The results suggest that the c-and -amino groups of the N-terminal L-lysyl residue interact stereospecifically with the DNA helix thus dictating the positioning of the aromatic ring of the C-terminal phenylalanine residue. In the accompanying paper (Gabbay et al, 1976), the interaction of several oligopeptides, containing the N-terminal L-Lys-L-Phe residue, with DNA is examined. The results are found to be consistent with stereospecific binding of the ter- The 1B NMR signal of the aromatic protons of L-Lys-L-PheA (1) and L-Lys-D-PheA (2) (a and b, respectively); in the absence (a) and presence of DNA at a base pair to peptide ratio of 7.5 (b), 3.6 (c), 2.4 (d), and 0.5 (e).…”
mentioning
confidence: 99%